Why not Turkey? An updated analysis of citizens’ attitudes towards Turkish membership in the EU - Gerhards, Jürgen; Hans, Silke (2011)
Abstract: "In a recently published article ('Why not Turkey? Attitudes towards Turkish Membership in the EU among Citizens in 27 European Countries', Journal of Common Market Studies 2011, DOI: 10.1111/j.1468‐5965.2010.02155.x), (the authors) described and explained the attitudes of citizens in the 27 member states of the EU towards Turkey’s possible membership in the EU. As more recent data are now available, this paper intends to give a brief update of the former analysis using EB 69.2 data from 2008." (author's abstract)